EFFECT ON THE PROMOTION AND PRICE ON DECISION TO PURCHASE OF RAILWAY AIRPORT TRANSPORT TICKETS - Zahara, Rita; Noor Sembiring (Dinasti Publisher, 2020)
The purpose of this study was to determine whether the promotions and price direct significant effect on purchasing decision of Railway transport service. This research was conducted by taking a sample of 96 respondents from a population of 2,000 passenger railway service. Data for this study were collected using questionnaires and analyzed by descriptive methods, multiple linear regression, hypothesis testing is used partially t-test and F test to test simultaneously with a significance level of 5%. Results from this study are the promotion of a significant effect on purchasing decisions. Price significant effect on purchasing decisions. Simultaneously sale prices and promotion have significant influence on purchasing decisions.